Successful balloon dilatation of an infolded polytetrafluoroethylene graft: An unusual cause of early Fontan failure - Saurabh Kumar Gupta; Sataroopa Mishra; Palleti Rajashekar; Sanjeev Kumar; Shyam Sunder Kothari (Wolters Kluwer Medknow Publications, 2023)
Despite optimal medical management, an 8-year-old boy had persistent pleural drainage following total cavopulmonary connection. Detailed evaluation, including computed tomography angiography, confirmed obstruction at the lower end of the circuit due to infolding of the polytetrafluoroethylene graft. Balloon dilation of the obstruction resulted in prompt resolution of pleural effusion with sustained relief at 1-year follow-up. The case demonstrates the importance of careful assessment in the diagnosis and successful nonsurgical management of an unusual cause of obstruction in the Fontan circuit.